Mak Nyahs in Malaysia: Does HIV/AIDS Knowledge Really Reduce HIV-Related Risk Behaviours? - S., Maliya; A.R., Zul; M.S., Irwan; D., Samsul; M.S., Zakiah; H.M., Rafidah (IIUM Medical Journal Malaysia, 2018)
Introduction. Male-to-female transgender individuals are known as mak nyahs in Malaysia. Akin to many other countries, mak nyahs face discriminations in securing proper employment, thus many end up in sex trade, exposing them to HIV-related high risk behaviours. This paper aims to investigate the knowledge, attitude, and risk behaviours in HIV/AIDS among mak nyahs in Malaysia. Method. Validated questionnaires in local language were used. Knowledge, attitude, and HIV-related risk behaviours were measured. With respondent-driven sampling method, 54 subjects participated in the survey. IBM SPSS was used for data analysis. Results. Majority of the subjects reported to have HIV-related sexual risk, although only a quarter were sex workers. Misconceptions still remained among the subjects. Inconsistent condom use was common. Adequate knowledge did result in better attitude towards HIV/AIDS. However, multiple regression analysis showed that subjects with higher knowledge in HIV/AIDS tend to have higher sexual risks (β = 0.320, p = 0.030). Conclusion. Educating the transgender community about HIV/AIDS does not seem to adequately reduce the HIV-related sexual risks. Other approaches, i.e. socio-cultural values and religious practices may be effective to instil higher levels of awareness and self-responsibility in this community to eliminate HIVrelated high risk behaviours.